High-purity production of ultrathin boron nitride nanosheets via shock chilling and their enhanced mechanical performance and transparency in nanocomposite hydrogels. (27th March 2018) - Sun, Zemin; Lin, Liu; Yuan, Mengwei; Li, Huifeng; Sun, Genban; Ma, Shulan; Yang, Xiaojing
Abstract: A simple, highly efficient, and eco-friendly method is prepared to divide bulk boron nitride (BN) into boron nitride nanosheets (BNNSs). Due to the anisotropy of the hexagonal BN expansion coefficient, bulk BN is exfoliated utilizing the rapid and tremendous change in temperature, the extreme gasification of water, and ice thermal expansion pressure under freeze drying. The thickness of most of the BNNSs was less than ∼3 nm with a yield of 12–16 wt%. The as-obtained BNNS/polyacrylamide (PAAm) composite hydrogels exhibited outstanding mechanical properties. The tensile strength is fives times the bulk of the BN/PAAm composite hydrogels and the elongations are more than nine-fold the bulk of the BN/PAAm composite hydrogels. The BNNS/PAAm nanocomposite hydrogels also exhibited excellent elastic recovery, and the hysteresis of the BNNS nanocomposite hydrogels was negligible even after 30 cycles with a maximum tensile strain ( ε max ) of 700%. This work provides new insight into the fabrication of BN/polymer nanocomposites utilizing the excellent mechanical properties and transparency of BN. The results confirm that a few layers of BNNSs can also efficiently and directly improve the mechanical properties of composite polymer due to its stronger surface free energy and better wettability.